Cerebroprotective effect of Glycyrrhiza glabra Linn. root extract - P. Muralidharan; G. Balamurugan; Venu Babu (Bangladesh Pharmacological Society, 2009)
The present study was carried out to evaluate the cerebroprotective effect of the aqueous extract of the roots of Glycyrrhiza glabra Linn. (250 and 500 mg/kg) in hypoxic rats. Hypoxia was induced by providing sodium nitrite drinking water to rats for 14 days. Extract at the tested doses promoted the locomotor activity and spatial behavior significantly, which was impaired in hypoxic rats. The extract administration restored the decreased levels of brain enzymes such as glutamate and dopamine and decreased acetylcholinesterase (AchE) activity significantly. Levels of antioxidant enzymes such as superoxide dismutase, glutathione peroxidase, glutathione reductase and catalase were reduced due to hypoxia and were restored to near normalcy by administration of ethanol extract of G. glabra. Increased lipid peroxidation in hypoxic rats was also restored significantly by extract treatment. Thus, this study suggests that ethanol extract of G. glabra possess a cerebroprotective effect in hypoxic rats, which may be mediated by its antioxidant effects.